LEGAL IMPLICATIONS OF DRUG USE IN TRADITIONAL MEDICINE BASED ON A HEALTH LAW PERSPECTIVE - Mariduk Lumban Tobing; Muhammad Azhali Siregar; Henry Aspan (International Journal of Synergy in Law, Criminal, and Justice, 2024)
The use of kratom and cannabis in traditional medicine has long been practiced, but it has now become the subject of debate due to the risk of misuse. Several countries, such as Thailand, have legalized cannabis for medical purposes, considering economic stability and public health. However, this legalization faces challenges, particularly concerning the increase in narcotics abuse. Therefore, it is essential to conduct a comprehensive evaluation of legalization policies, balancing the medical benefits and the risks of misuse, with strict regulation and effective oversight. In Indonesia, the legalization of cannabis remains a sensitive issue, strictly governed by Law No. 35 of 2009. Based on data on narcotics seizures, including cannabis and Methamphetamine, rational criminal policies are crucial to controlling drug circulation and ensuring that legalization, if implemented, supports both public health and economic welfare.